2019
DOI: 10.1177/2325967118822452
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Arthroscopic Posterior Shoulder Stabilization in the Beach-Chair Versus Lateral Decubitus Position: A Systematic Review

Abstract: Background:Arthroscopic posterior shoulder stabilization can be performed with patients in the beach-chair (BC) and the lateral decubitus (LD) positions; however, the impact of patient positioning on clinical outcomes has not been evaluated.Purpose:To compare clinical outcomes and recurrence rates after arthroscopic posterior shoulder stabilization performed in the BC and LD positions.Study Design:Systematic review; Level of evidence, 4.Methods:A systematic review using PRISMA (Preferred Reporting Items for Sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 43 publications
(187 reference statements)
1
17
1
Order By: Relevance
“…Our results show that the rate of return to duty slightly lags behind the rates of return to sport in studies of athletes. A recent systematic review by Moeller et al 17 revealed an 89% to 96% rate of return to sport in athletes after undergoing posterior stabilization surgery at a mean follow-up of 37.6 months. In the largest prospective study to date on arthroscopic posterior stabilization in athletes, Bradley et al 2 showed a 93.5% success rate in return to play after posterior stabilization in 200 NOTE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results show that the rate of return to duty slightly lags behind the rates of return to sport in studies of athletes. A recent systematic review by Moeller et al 17 revealed an 89% to 96% rate of return to sport in athletes after undergoing posterior stabilization surgery at a mean follow-up of 37.6 months. In the largest prospective study to date on arthroscopic posterior stabilization in athletes, Bradley et al 2 showed a 93.5% success rate in return to play after posterior stabilization in 200 NOTE.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, we cannot make true determinations based on our data alone, but we can make comparisons with existing literature. Regarding intraoperative patient positioning, Moeller et al 17 performed a systematic review comparing outcomes in patients who underwent arthroscopic posterior stabilization in either the beachchair or lateral decubitus position. They found no differences in patient outcome scores or rates of recurrent instability or return to sport.…”
Section: Discussionmentioning
confidence: 99%
“…There was also no difference in the rate of identified posterior pathology when comparing procedures performed in the beachchair and lateral positions, an outcome consistent with prior authors' findings. [13][14][15] Of particular interest, combined anterior and posterior lesions were more likely following two or fewer dislocations rather than in individuals that had suffered multiple prior instability events. One possible explanation for this finding is that the encountered posterior pathology may have occurred prior to traumatic dislocation.…”
Section: Discussionmentioning
confidence: 99%
“…Other technical factors may include patient positioning, 39 arthroscope orientation, 51 bone-tendon contact pressure, 17 anchor type, 43 or suture type and strength, 22 all of which have been studied as independent factors with the potential to affect the outcome of a procedure. Additionally, wet conditions within the joint can lead to increased friction of the suture material, 9 and knot security may ultimately be reduced compared with hand-tied knots by the requisite use of instrumentation.…”
Section: Discussionmentioning
confidence: 99%